Adipose Tissue Macrophage Polarization in Healthy and Unhealthy Obesity - Ruggiero, Alistaire D.; Key, Chia-Chi Chuang; Kavanagh, Kylie (Frontiers in Nutrition, 2021)
Over 650 million adults are obese (BMI > 30mg/m2) worldwide. Obesity is commonly associated with several comorbidities, including cardiovascular disease and type II diabetes. However, compiled estimates suggest that between 5-40% of obese individuals do not experience metabolic or cardiovascular complications. The existence of the metabolically unhealthy obese (MUO) and the metabolically healthy obese (MHO) phenotypes suggests that underlying differences exist in both tissues and overall systemic function. Macrophage accumulation in white adipose tissue (AT) in obesity is typically associated with insulin resistance. However, as plastic cells, macrophages respond to stimuli in their microenvironments, altering their polarization between pro- and anti-inflammatory phenotypes, depending on the state of their surroundings. The dichotomous nature of MHO and MUO clinical phenotypes suggests that differences in white AT function dictate local inflammatory responses by driving changes in macrophage subtypes. As obesity requires extensive AT expansion, we posit that remodeling capacity with adipose expansion potentiates favorable macrophage profiles in MHO as compared with MUO individuals. In this review, we discuss how differences in adipogenesis, AT extracellular matrix deposition and breakdown, and AT angiogenesis perpetuate altered AT macrophage profiles in MUO compared to MHO. We discuss how non-autonomous effects of remote organ systems, including the liver and cardiovascular system, interact with white adipose favorably in MHO. Preferential AT macrophage profiles in MHO stem from sustained AT function and improved overall fitness and systemic health.